Direct TLC Enantioseparations of Four Neutral Aliphatic DL-Amino Acids Using Teicoplanin as Chiral Selector - Yuan, Chen (Asian Journal of Chemistry, 2015)
TLC experiments were performed to resolve the enantiomers for four neutral aliphatic DL-a-amino acids, DL-alanine, DL-valine, DL-leucine and DL-isoleucine on silica gel plates using teicoplanin as chiral selector with same developing solvent n-butanol-methanol-water (5:0.5:1.2, v/v). The effects of constitute of developing solvents, the ratio of mobile phase, concentration of chiral selector and temperature on the enantioseparation had been studied. To our best of knowledge, this is the first report on thin layer chromatographic chiral resolution using teicoplanin as the chiral selector.